Practice of Professional Values of Hospital Nurses in Bacolod City - Sosas, Myra; Gosiengfiao, Neifertiti B. (Technium Social Sciences Journal, 2021)
This study assesses the extent of the practice of professional values of hospital nurses in Bacolod City using descriptive, comparative and correlational design. Furthermore, it compares the extent of practice of nurses' professional values and the designation of assessors. It also determines whether a significant relationship exists between the respondents' demographic profile and the practice of professional values of hospital nurses. Using a researcher-made survey questionnaire, the data were analyzed using frequency count, percentage distribution, mean, standard deviation, Mann-Whitney U test and Spearman rank correlation. The findings reveal that the practice of professional values of hospital nurses is very great extent with social justice being the highest while altruism being the lowest. No significant difference was found in the extent of practice of professional values when assessors are grouped according to designation. However, a significant relationship was found between sex, age, and practice of professional values of hospital nurses; nevertheless, no significant relationship was found between civil status, years of experience, educational level, and practice professional values. Lastly, the most significant challenge encountered by hospital nurses was prolonged working hours (>8hours/day).